Relationship between cardiac fibroblast activation protein activity by positron emission tomography and cardiovascular disease - Heckmann, Markus B.; Reinhardt, Finn; Finke, Daniel; Katus, Hugo; Haberkorn, Uwe; Leuschner, Florian; Lehmann, Lorenz (Circulation. Cardiovascular imaging, 2020)
Background: FAP (fibroblast activation protein) plays an important role in cardiac wound healing and remodeling. Although initially developed as a theranostic ligand for metastasized cancer, FAPI (FAP inhibitor) tracers have recently been used to study cardiac remodeling following myocardial infarction in small-animal models. The aim of the study was to evaluate the activity of FAP via FAPI-positron emission tomography-computed tomography scans in human hearts. Methods: FAPI-positron emission tomography-computed tomography scans of 229 patients of 2 consecutive cohorts (modeling cohort: n=185; confirmatory cohort: n=44) suffering from metastasized cancer were analyzed applying the American Heart Association 17-segment model of the left ventricle. Logistic regression models were created using data from the modeling cohort. Multivariate regression models were established using Akaike information criterion in a step-down approach. Results: Fourteen percent of patients had preexisting coronary artery disease (n=31), 33% arterial hypertension (n=75), and 12% diabetes mellitus type II (n=28). Forty-three percent had been treated with platin derivatives (n=100), 14% with anthracyclines (n=32), and 10% had a history of prior radiation to the chest (n=23). High left ventricular FAPI signals correlated with the presence of cardiovascular risk factors (odds ratio [OR], 4.3,P=0.0029), a focal myocardial signal pattern (OR, 3.9,P=0.0068), diabetes mellitus type II (OR, 4.1,P=0.046), and beta-blocker use (OR, 3.8,P=0.049) in univariate regression models. In a multivariate analysis, increased signal intensity was significantly higher in patients with cardiovascular risk factors (overweight [OR, 2.6,P=0.023], diabetes mellitus type II [OR, 2.9,P=0.041], certain chemotherapies [platinum derivatives; OR, 3.0,P=0.034], and a history of radiation to the chest [OR, 3.5,P=0.024]). A focal enrichment pattern was more frequently observed in patients with known cardiovascular risk factors (P<0.0001). Conclusions: FAPI-positron emission tomography-computed tomography scans represent a new imaging modality to investigate cardiac FAP. High signal intensities correlate with cardiovascular risk factors and metabolic disease.